Perioperative Lung Protection: Clinical Implications. (December 2020) - Hol, Liselotte; Nijbroek, Sunny G. L. H.; Schultz, Marcus J.
Abstract : In the past, it was common practice to use a high tidal volume (VT ) during intraoperative ventilation, because this reduced the need for high oxygen fractions to compensate for the ventilation-perfusion mismatches due to atelectasis in a time when it was uncommon to use positive end-expiratory pressure (PEEP) in the operating room. Convincing and increasing evidence for harm induced by ventilation with a high VT has emerged over recent decades, also in the operating room, and by now intraoperative ventilation with a low VT is a well-adopted approach. There is less certainty about the level of PEEP during intraoperative ventilation. Evidence for benefit and harm of higher PEEP during intraoperative ventilation is at least contradicting. While some PEEP may prevent lung injury through reduction of atelectasis, higher PEEP is undeniably associated with an increased risk of intraoperative hypotension that frequently requires administration of vasoactive drugs. The optimal level of inspired oxygen fraction (FIO2 ) during surgery is even more uncertain. The suggestion that hyperoxemia prevents against surgical site infections has not been confirmed in recent research. In addition, gas absorption-induced atelectasis and its association with adverse outcomes like postoperative pulmonary complications actually makes use of a high FIO2 less attractive. Based on the available evidence, we recommend the use of a low VT of 6–8 mL/kg predicted body weight in all surgery patients, and to restrict use of a high PEEP and high FIO2 during intraoperative ventilation to cases in which hypoxemia develops. Here, we prefer to first increase FIO2 before using high PEEP.